Symptoms, impacts, and suitability of the Pulmonary Arterial Hypertension - Symptoms and Impact (PAH-SYMPACT™) questionnaire in patients with chronic thromboembolic pulmonary hypertension (CTEPH): a qualitative interview study - Brooke Currie; Evan Davies; Amélie Beaudet; Larissa Stassek; Leah Kleinman (SpringerOpen, 2021)
Abstract Background Chronic thromboembolic pulmonary hypertension (CTEPH) is a rare form of pulmonary hypertension caused by blood clots and scar tissue in the blood vessels of the lungs. Health-related quality of life is often significantly impaired in patients with CTEPH. However, a better understanding of how CTEPH symptoms affect patients' lives is needed to optimally assess the impact of the disease and treatment. Objectives This qualitative study aimed to better understand the symptoms of CTEPH and how they affect patients' lives, as well as to determine the appropriateness of the Pulmonary Arterial Hypertension - Symptoms and Impact (PAH-SYMPACT™) questionnaire for use in this patient population. Methods Adults diagnosed with CTEPH, recruited from two clinical sites in the US, participated in one-to-one qualitative telephone interviews. They described their experience of CTEPH symptoms and the impact these symptoms have on their lives. They also provided feedback on the comprehensibility and relevance of the PAH-SYMPACT™'s instructions, items, and response options. Results Participants (N = 12) had a mean age of 62.5 years. Two thirds were female and most (83%) had undergone pulmonary endarterectomy and/or balloon pulmonary angioplasty. The most frequently endorsed symptoms were shortness of breath (endorsed by all 12 participants), fatigue (11 participants), and lightheadedness (10 participants). All participants identified shortness of breath as an "extremely important" symptom, and seven participants rated fatigue as "extremely important." The most frequent impacts of CTEPH were on ability to walk quickly (endorsed by all 12 participants), ability to walk up inclines or stairs (11 participants), and ability to carry things (11 participants). The PAH-SYMPACT™ items were relevant to most participants and reflected their experience of CTEPH. All participants indicated that no important CTEPH symptoms were missing from the PAH-SYMPACT™. Overall, the instructions, items, and response options of the PAH-SYMPACT™ were clear and easy to understand. Conclusions The symptoms and impacts experienced by patients with CTEPH align with items included in the PAH-SYMPACT™. The PAH-SYMPACT™ appears to be fit for purpose for assessing disease status in patients with CTEPH.